Fundamentals of T Cell Metabolism and Strategies to Enhance Cancer Immunotherapy - Rangel Rivera, Guillermo O.; Knochelmann, Hannah M.; Dwyer, Connor J.; Smith, Aubrey S.; Wyatt, Megan M.; Rivera-Reyes, Amalia M.; Thaxton, Jessica E.; Paulos, Chrystal M. (Frontiers in Immunology, 2021)
Emerging reports show that metabolic pathways can be targeted to enhance T cell-mediated immunity to tumors. Yet, tumors consume key metabolites in the host to survive, thus robbing T cells of these nutrients to function and thrive. T cells are often deprived of basic building blocks for energy in the tumor, including glucose and amino acids needed to proliferate or produce cytotoxic molecules against tumors. Immunosuppressive molecules in the host further compromise the lytic capacity of T cells. Moreover, checkpoint receptors inhibit T cell responses by impairing their bioenergetic potential within tumors. In this review, we discuss the fundamental metabolic pathways involved in T cell activation, differentiation and response against tumors. We then address ways to target metabolic pathways to improve the next generation of immunotherapies for cancer patients. Introduction